Analisis Peran Pesantren dalam Mengimplementasikan Pasal 37 - 42 UU No. 18 Tahun 2019 Tentang Pesantren - Herlina, Lenny (ANWARUL, 2021)
This paper attempts to analyze the role of Islamic boarding schools in implementing the Indonesian government's policies on religious and religious education as stated in UU no. 18 of 2019 concerning Islamic boarding schools, focusing on the fifth part of articles 37-42 regarding the role of Islamic boarding schools. Pondok Pesantren is one of the educational, da'wah and social institutions of Islam in the archipelago aimed at forming quality human beings, cadres of ulama and preachers. This study focuses on Pesantren as a da'wah institution, by setting out on questions related to how pesantren accommodates pasal-pasal referred to in an effort to achieve its goal of producing quality ulamak and da'i cadres. and what should be done by pesantren and the government in order to achieve this goal.